Implementasi Nilai-Nilai Islam dalam Mengatasi Krisis Adab Mahasiswa di Lingkungan Kampus UIN Walisongo - Rheyna Putri Tazkiyyah; Melinda Wahyu Ningrum; M. Rikza Chamami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The crisis of student morality and etiquette in higher education institutions has become an increasingly concerning phenomenon in the modern era. Social changes, the rapid development of digital technology, and the weakening The crisis of student morality and etiquette in higher education institutions has become an increasingly concerning phenomenon in the modern era. Social changes, the rapid development of digital technology, and the weakening internalization of religious values have contributed to a decline in students' moral character, which is reflected in poor communication ethics, lack of respect for lecturers, plagiarism practices, individualistic attitudes, and weak academic responsibility. This study aims to analyze the implementation of Islamic values in addressing the crisis of student etiquette at UIN Walisongo Semarang. The research employs a qualitative approach with a descriptive method through literature review, observation, and data collection from various scientific journals. The findings indicate that the implementation of Islamic values, such as akhlaq al-karimah (noble character), trustworthiness (amanah), discipline, Islamic brotherhood (ukhuwah Islamiyah), and responsibility, can serve as effective solutions in developing students' religious and ethical character. These values are implemented through spiritual development programs, an Islamic academic culture, lecturers' role modeling, Islamic student organization activities, and character education based on Islamic principles. This study emphasizes that the integration of Islamic values into the campus education system constitutes a strategic step in shaping a generation of Muslim intellectuals who excel not only academically but also possess strong morality and ethical conduct.